Text-fig. 4. a–e: Parrotia aff. persica. a: Oriolo MSF 991 capsule. b: Oriolo MSF 994 endocarp. c: Oriolo MSF 654. d: Oriolo MSF 743. e: Oriolo MSF 678. f: Vitis sp. Oriolo MSF 838. g–k: Gleditsia aff. caspica. g: Oriolo MSF 920. h: Oriolo MSF 939. i: Oriolo MSF 787. j: Oriolo MSF 917. k: Oriolo MSF 925. Scale bars 10 mm (a, h–k), 5 mm (b), 50 mm (c–f). in The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome - Denk, Thomas; Sami, Marco; Teodoridis, Vasilis; Martinetto, Edoardo (Zenodo, 2022)
Text-fig. 4. a–e: Parrotia aff. persica. a: Oriolo MSF 991 capsule. b: Oriolo MSF 994 endocarp. c: Oriolo MSF 654. d: Oriolo MSF 743. e: Oriolo MSF 678. f: Vitis sp. Oriolo MSF 838. g–k: Gleditsia aff. caspica. g: Oriolo MSF 920. h: Oriolo MSF 939. i: Oriolo MSF 787. j: Oriolo MSF 917. k: Oriolo MSF 925. Scale bars 10 mm (a, h–k), 5 mm (b), 50 mm (c–f). Published as part of Denk, Thomas, Sami, Marco, Teodoridis, Vasilis & Martinetto, Edoardo, 2022, The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome, pp. 217-262 in Fossil Imprint 78 (1) on page 226, DOI:10.37520/fi.2022.009, http://zenodo.org/record/7167867